Efektivitas Konseling Individual Pendekatan Behavioristik dalam Mengatasi Prokrastinasi Akademik Siswa - Donal Donal; Yeni Karneli; Desva Rofiah As’ari; Ramadhan Aulia Puri (Jurusan Tarbiyah dan Pendidikan, 2026)
Academic procrastination is a learning behavior problem that affects students' discipline, task completion, and learning engagement. This study aims to understand the process of behavioral change in a student experiencing academic procrastination through individual counseling with a behavioral approach using self-management techniques. This study employed a qualitative approach with a case study design on one vocational high school student selected purposively for exhibiting characteristics of academic procrastination. Data were collected through behavioral observation, interviews with the student, the school counselor, and the homeroom teacher, as well as documentation of behavioral development, and were analyzed using the Miles and Huberman model through data reduction, data display, and conclusion drawing. Data trustworthiness was ensured through source and technique triangulation. The results show concrete behavioral changes after the intervention, namely improved attendance discipline, reduced smartphone use during lessons, increased ability to complete assignments independently, greater learning participation, and stronger self-control. Behavioral counseling through self-management techniques helped the student recognize maladaptive behaviors, set behavioral targets, conduct self-monitoring, and build more adaptive learning habits.